Enabling equitable access to canal water resources in coastal Bangladesh - Sarker, Mou Rani; Joshi, Deepa; Mannan, Fouzia; Rahman, M. Mokhlesur (CGIAR Initiative on Asian Mega-Deltas, 2024)
Key messages